The Role of Entrepreneurial Mindset in Facing Market Uncertainty in New Entrepreneurs - Eni Widhajati (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study examines the role of entrepreneurial mindset in helping new entrepreneurs deal with market uncertainty. New entrepreneurs often face significant challenges in adapting to rapidly changing market dynamics. Through a literature review and case study analysis, this study shows that an entrepreneurial mindset that focuses on innovation, risk-taking, and flexibility enables entrepreneurs to respond to change more effectively. The results of this study reveal that entrepreneurial mindset plays a significant role in strategic decision-making that minimizes the negative impacts of market uncertainty. The conclusion of this study provides recommendations for new entrepreneurs to develop an entrepreneurial mindset as one of the main strategies in maintaining business growth and sustainability.